The Role of Diploma I Cadastral Surveying and Mapping Program in Fulfilling the Needs of Cadastral Surveyor Assistant in Indonesia - Aisiyah, Nuraini; ., Kusmiarto (International Journal of Engineering and Technology, 2018)
This paper aims to describe the role of Diploma I Cadastral Surveying and Mapping Program of National Land College (DI PPK- STPN) in fulfilling the needs of Cadastral Surveyor Assistant in Indonesia. DI PPK-STPN was established in 1996 in Yogyakarta with the aim to meet the needs of Cadastral Surveyor Assistant in Adjudication Program. Previously, in Indonesia, the candidate of Cadastral Surveyor Assistant was educated through the short course program. The method is descriptive, informative, which describes ability and competence owned by alumni of Diploma I PPK-STPN. Identification of the number of alumni of Diploma I PPK-STPN can describe the number of Cadastral Surveyor Assistant of Indonesia. By looking at the number of alumni of Diploma I PPK-STPN, we can see the level of adequacy of the needs of Cadastral Surveyor Assistant in the acceleration program of land registration in Indonesia. To achieve the ideal number of Cadastral Surveyor Assistant in Indonesia, the existence of DI PPK-STPN is still needed.Â Â